ANALISIS PERHITUNGAN HARGA JUAL ASESORIS – KALUNG KREASIOLIN DI INSTAGRAM - Megasari NSC, Ita (JBT (JURNAL BISNIS dan TEKNOLOGI), 2024)
This study aims to determine the calculation of the selling price of Kreasiolin necklace accessories whose promotional media uses social media. The utilization of technology and communication such as smartphones is very easy for the business world in running its business, including being able to reach a wide market share, being able to easily control the business anywhere / not just sitting at home, smartphones can be easily operated, and many other benefits.The results of this study indicate that Kreasiolin already has a computerized recording system in recording income and costs, so the information provided is quite reliable. However, the information on the calculation of cost of production has not referred to cost accounting standards so that the determination of Kreasiolin's selling price is not correct and will have an impact on the profit earned.